The Role of Parents in Learning to Read and Write for Class 2 Students at State Elementary School 002 Kotobaru - Maini Irtiyah; Febrina Dafit (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the role of parents in learning to read and write grade 2 elementary school students. The method used is a qualitative research type of case study. Data collection techniques are observation, interviews and documentation. Testing the validity of the data using source triangulation and technical triangulation. The data analysis technique used is data collection, data reduction, data presentation and conclusions. The conclusion of this study is that learning to read and write is a basic skill that must be mastered by students. There are 4 roles of parents, namely acting as facilitators to see what parents have prepared to meet the reading and writing needs of students, and parents also acting as educators who can replace the role of teachers when they are at home, then parents as mentors who can guide children's learning and supervise in learning. reading and writing activities and finally the role of parents as motivators and advisors, namely to help children stay enthusiastic in learning to read and write so as not to give up, with that parents of grade 2 students at State Elementary School 002 Kotobaru have played a good role in improving reading and writing skills